Seleksi Berbagai Genotipe Jagung Manis, Cabai dan Kacang Panjang Hasil Pemuliaan IPB sebagai Penyedia Benih Unggul - Undang Undang (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2012)
Collection and selection are important steps in a breeding activity series. The purpose of this research is to produce new superior varieties of sweet corn, chilli and cowpea, as this research is also a bridge between researchers/lecturers (seed producer) and farmers (seed users). This research was conducted in Gunung Gede experimental garden, IPB Diploma Programs, commenced from August to December 2010. The genetic materials used are 1 (one) genotype of corn, 10 genotypes of cowpea, and 12 genotypes of chilli. The plant materials are strains produced by the Plant Breeding and Genetics Laboratory of Agronomy and Horticulture Department, IPB. The experiment was done in Randomized Block Complete Design, one factor is genotype. The negative and positive selection was applied on sweet corn selection, while the index selection was applied on chilli and cowpea. Selection on corn (with 20% of selection proportion) produced 30 best plants. This step can be used as a startup to get the next population (with upturned genetics) to be better. The 5002046 is the best chilli genotype; meanwhile Cilibende, Kencana, K7 and Majalengka are the best cowpea genotypes. Selected chilli and cowpea genotypes are candidat lines for good seed production.Keywords: corn, cowpea, chili, seed, selection.